Investigating the Therapeutic Potential of Jal Neti and Rapid Kapalbhati for Managing Sinus and Ocular Issues - Meena, Dinesh Kumar; kanwar, Sharda (International Research Journal of Ayurveda & Yoga, 2025)
Background: In this research study, the use of traditional yogic practices such as Jala Neti and Rapid Kapalabhati is proposed as potential complementary treatments for sinusitis and ocular issues which have become very common nowadays. This research work is based on experimental qualitative research design and aims to investigate the therapeutic potential of Jala Neti and Rapid Kapalabhati for the management of sinus and ocular issues. Methods: The research work included 34 participants aged 22–58 years who self-reported sinusitis and ocular issues. The participants were prescribed an intervention program of regular practice of Jala Neti and Rapid Kapalabhati for 6 weeks. Data collection of changes in symptoms related to the problems was done using qualitative methods through semi-structured interviews of the participants to assess the efficacy of this yogic intervention program. Results: The findings of the research study clearly indicate a reduction in sinus-related symptoms such as nasal congestion, facial pain, postnasal drip, and nasal congestion. There was also an improvement in ocular issues including dryness, itching, blurred vision, and redness of the eyes. The willingness with which the intervention protocol was accepted by the participants indicates the efficacy of Jala Neti and Rapid Kapalabhati as complementary treatments for the management of sinus and ocular issues. Conclusion: The findings of this study provide preliminary evidence supporting the therapeutic potential of Jala Neti and Rapid Kapalabhati for the management of sinus and ocular issues. The practice of these yoga practices, if adopted as an additional option in one’s lifestyle, can play an important role in the treatment of sinus and ocular issues.